2018
DOI: 10.4995/wrs.2018.9587
|View full text |Cite
|
Sign up to set email alerts
|

Are combi parks just as useful as regular parks for fatteners for part-time group housing of rabbit does?

Abstract: <p>Group housing of lactating rabbit does is desirable from a welfare standpoint, but agonistic behaviour can cause severe skin injuries, which are undesired for animal welfare. Park layout, creating hiding places and escape possibilities, may help redirect attention away from fighting, which could in turn help prevent skin damage. An experiment was performed to test whether more damaging behaviour would occur in a combi park (with nest box panels) after mixing, compared to a regular park for fatteners, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Does in late lactation may be less stressed, since more time has passed after kindling and the presence of the kits out of nest boxes may positively modulate female to female aggression (Zomeno et al, 2017). Nevertheless, Rommers and de Greef (2018) found that the percentage of injured does in a part-time system with 5 does increased Welfare of rabbits on-farm www.efsa.europa.eu/efsajournal from 34% measured 4 days after group formation (23 days of lactation) to 53% at litter weaning (36 days) (Table 30).…”
Section: Reproducing Doesmentioning
confidence: 99%
“…Does in late lactation may be less stressed, since more time has passed after kindling and the presence of the kits out of nest boxes may positively modulate female to female aggression (Zomeno et al, 2017). Nevertheless, Rommers and de Greef (2018) found that the percentage of injured does in a part-time system with 5 does increased Welfare of rabbits on-farm www.efsa.europa.eu/efsajournal from 34% measured 4 days after group formation (23 days of lactation) to 53% at litter weaning (36 days) (Table 30).…”
Section: Reproducing Doesmentioning
confidence: 99%
“…In some European countries, new rules are being implemented; the transition towards new housing systems to provide better living conditions is already taking place (European Commission, 2017). Moreover, this housing system is usually better valued by some consumers, paying a higher price for rabbits produced under more friendly conditions (Rommers and De Greef., 2018). Some alternate housing systems have been proposed, whose main goals is to increase the useful area, the activity level and to improve the behaviour of the housed animals.…”
Section: Introductionmentioning
confidence: 99%
“…One system is based on an individual cage with a platform, improving the total area without the need to increase the dimensions of the current farms to house the same number of rabbits does. This collective housing system is gaining prominence (Szendrő et al, 2016;Rommers and De Greef, 2018;Zomeño et al, 2018;Szendrő et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations